A novel homogeneous stacked yttrium ion garnet resonator antenna for wideband application. Issue 12 (22nd September 2017) - Othman, Mohamadariff; Ali, Wan Fahmin Faiz Wan; Ahmad Zubir, Ihsan; Ain, Mohd Fadzil; Ahmad, Zainal Arifin
Abstract: The intent of this study is to realize efficient wideband DRA using unbiased low permittivity yttrium ion garnet (YIG) with excess Fe2 O3 . The fabricated YIG resonators with the same dimension but different ɛr are used together to produce wideband stacked YIG resonator antenna (YRA). Three stacked YIG resonators with excess Fe2 O3 of 8% (YR8), 14% (YR14), and 17% (YR17) present the best YIG resonator combinations with bandwidth of 24.22%. Findings also indicate broadband radiation pattern throughout the design frequency range. The simulated and measured results are all in agreement. In conclusion, this work offers an improved and efficient YRA using YIG resonator with excess Fe2 O3 .